Kongjian Yu and the redefinition of china's cultural landscape - Jover Biboum, Margarita; García Rubio, Rubén; ´Ávila Calzada, Carlos (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
As a result of his important career abroad and his family experiences in his home province of Zhejiang, Kongjian Yu reflects in this interview on the need to look at and learn from the past, from tradition, in order to restore harmony to our relationship with the environment in which we live. Learning from the environment as a means of providing project solutions that are adapted to the very drastic changes that we are experiencing. All this with a global and local perspective, always valuing the strategies that can be applied in other territories, adapting them to the idiosyncrasy of the place. To this end, Kongjian Yu raises the need to train new professionals who know how to work with the variables we are facing in the context of the current environmental crisis, changing the dynamics established in professional and political circles.
Keywords: Water; Cultural Landscape; China; Landscape Architecture